Remote sensing analysis of the spatio-temporal growth of Ibadan city between 1984 and 2006 (2010)
This study focussed on the capability of medium resolution satellite imageries to map out the spatial pattern of the growth of cities in developing countries, where real time data on city growth is absent, or at best, scarce. Landsat TM and ETM for 1984 - 2006 were used in delineating the pattern of urban growth. Unsupervised and latter supervised algorithms were used in identifying the extent of growth of the city. A vector change analysis technique was used to analyse changes in the spatial growth of the city among and between the different administrative units, and the different years under consideration. The result of the study showed a 6.64% annual growth for the city, while the highest level of urbanization was found in Akinyele, Ido, and Oluyole Local Government Areas, respectively. In addition, using Markov chain modelling approach, the growth rate of the city was predicted. The growth prediction of the city of Ibadan was based on the historical trends observed between 1984 and 2006, under the current policy constraints and the physical environment. The predicted urbanization also showed that by 2028, Ido LGA would have surpassed the other two LGAs in its urban growth.